Cloned buffalo bulls and their somatic cell donor bulls exhibit similar in-vitro embryo production efficienc - Tanya Gupta; Gaurav Tripathi; Sonal Gupta; Naresh L. Selokar; Manoj Kumar Singh (Revista Científica)
Somatic cell nuclear transfer (SCNT) has emerged as a valuable assisted reproductive technology for faster multiplication of animals. This helps to preserve the valuable superior germplasm. The cloning of superior sires and their use in breeding programs helps rapidly disseminate superior genetics in animal populations. However, questions remain regarding cloned bulls’ fertility status compared to their somatic cell donor bulls, especially in buffaloes. We studied the semen kinetic parameters and in vitro fertilization (IVF) rate of frozen-thawed cloned bulls’ semen (n=2) compared to those of somatic cell donor bulls’ semen (n=2). The kinematics were studied  using a Computer Assisted Semen Analyzer (CASA; IVOS II, IMV, France). Semen from cloned bulls vs. donor bulls showed progressive motility with distance average path (17.70 ± 0.835 vs. 18.72 ± 0.53 μm), distance curvilinear (28.30 ± 2.85 vs. 31.61 ± 1.71 μm), distance straight line (15.89 ± 0.56 vs. 16.36 ± 0.20 μm), velocity average path (74.84 ± 7.23 vs 69.59 ± 9.96 μm/s), velocity curvilinear (113.77 ± 15.28 vs 113.49 ± 16.94 μm/s), and velocity straight line (66.71 ± 6.01 vs. 61.94 ± 9.13 μm/s). This suggested that the kinematic parameters of cloned bull semen were not significantly different (p<0.05) from those of the somatic cell donor bull semen. Furthermore, cloned and donor bull semen was used for IVF to assess the blastocyst production rate. Immature oocytes were matured in vitro for 24 h in a humidified CO2 incubator (5% CO2 in air; RH>95%) at 38.5°C. After 24 h, mature oocytes were co-incubated with processed semen in the fertilization Bracket and Oliphant (BO) medium for 18 h. The presumptive zygotes were cultured in Research Vitro Cleavage medium (RVCL; Cook, Australia) for up to 8 days. The cleavage and blastocyst rates for cloned bulls, 68.72 ± 0.72% and 14.11 ± 1.89%, respectively, did not differ significantly (p<0.05) from those of the donor bulls, i.e., 67.44 ±0.16% and 13.96 ± 1.24%, respectively. Furthermore, the expression of pluripotency-related genes (OCT4, SOX2, and NANOG) was similar in blastocysts produced in both experimental groups. Thus, the semen characteristics and in vitro embryo production rate of cloned bulls are like those of their somatic cell donor bulls. This preliminary study suggests that farmers can use semen from cloned bulls for Artificial Insemination programs and other ART procedures.